Internalisasi Nilai Ihsan sebagai Fondasi Character Sustainability dalam Pendidikan Agama Islam - Mahesa Zidan; Iqbal Amar Muzaki; Yadi Fahmi Arifudin (EduInovasi: Journal of Basic Educational Studies, 2026)
The sustainability of character education has become a central issue in the era of globalization and digital transformation. Islamic Religious Education (IRE) plays a crucial role in developing sustainable character grounded in spiritual awareness. This study aims to analyze the internalization of the value of ihsan as a foundation for character sustainability in Islamic education. Using a qualitative library research approach, this study examines scholarly works published between 2021–2025 related to Islamic character education, value internalization, and sustainability frameworks. The findings indicate that ihsan—understood as spiritual consciousness (muraqabah), excellence in action, and ethical benevolence—serves as a transformative moral force when internalized through habituation, role modeling, curriculum integration, and school culture. The concept of character sustainability refers to consistent moral behavior that persists beyond external supervision and adapts to global challenges. Therefore, the integration of ihsan values into Islamic education provides a holistic and sustainable character-building framework capable of strengthening students’ moral resilience in contemporary society.